Kinematics of Active Deformation Across the Western Kunlun Mountain Range (Xinjiang, China) and Potential Seismic Hazards Within the Southern Tarim Basin - Guilbaud, Christelle (2018)
The Western Kunlun mountain range is a slowly converging intracontinental orogen where deformation rates are too low to be properly quantified from geodetic techniques. This region has recorded little seismicity, but the recent July 2015 (Mw 6.4) Pishan earthquake shows that this mountain range remains seismic. To quantify the rate of active deformation and the potential for major earthquakes in this region, we combine a structural and quantitative morphological analysis of the Yecheng–Pishan fold, along the topographic mountain front in the epicentral area. Using a seismic profile, we derive a structural cross section in which we identify the fault that broke during the Pishan earthquake, an 8–12 km deep blind ramp beneath the Yecheng–Pishan fold. Combining satellite images and DEMs, we achieve a detailed morphological analysis of the Yecheng–Pishan fold, where we find nine levels of incised fluvial terraces and alluvial fans. From their incision pattern and using age constraints retrieved on some of these terraces from field sampling, we quantify the slip rate on the underlying blind ramp to 0.5 to 2.5 mm/yr, with a most probable long-term value of 2 to 2.5 mm/yr. The evolution of the Yecheng–Pishan fold is proposed by combining all structural, morphological, and chronological observations. Finally, we compare the seismotectonic context of the Western Kunlun to what has been proposed for the Himalayas of Central Nepal. This allows for discussing the possibility of M ≥ 8 earthquakes if the whole decollement across the southern Tarim Basin is seismically locked and ruptures in one single event.